Age and growth of the blue shark (Prionace glauca) in the Indian Ocean - Andrade, Inês (2020)
Since there is still a lack of biological information regarding Prionace glauca in the Indian Ocean, specifically in terms of age estimation and growth modelling, the age and growth of this species was studied by analysing vertebral samples. All samples were collected from specimens captured by pelagic longliners between March 2013 and September 2016, with sizes ranging from 82 to 301 cm fork length (LF). Two growth models were fitted to the age data, a three-parameter von Bertalanffy growth function (VBGF) re-parameterized to calculate L0 (size at birth) and a two-parameter VBGF with a fixed L0. The latter was considered the most adequate to describe the growth of the species, with the estimated parameters being L∞ = 283.8 cm LF, k  = 0.13 year−1 for males and L∞ = 290.6 cm LF, k = 0.12 year−1 for females. These results suggest that females have a slower growth than males. The maximum age estimated was 25 years, representing the oldest attributed age to this species so far. Further work is needed regarding P. glauca in the Indian Ocean, but this study adds important life-history information that can contribute for the management and conservation of the species.